2005
DOI: 10.1562/2005-01-25-ir-427
|View full text |Cite
|
Sign up to set email alerts
|

Intercalation of Organic Dye Molecules into Double‐stranded DNA. Part 2: The Annelated Quinolizinium Ion as a Structural Motif in DNA Intercalators

Abstract: DNA intercalators represent an important class of compounds with a high potential as DNA-targeting drugs. In this review it is demonstrated that annelated quinolizinium derivatives such as coralyne and derivatives thereof intercalate into DNA and that this structural motif allows several variations of the substitution pattern without loss of intercalating properties. The commonly applied methods for the evaluation of the DNA association, mainly spectroscopic studies, are pointed out. In addition, studies on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
102
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 109 publications
(103 citation statements)
references
References 57 publications
1
102
0
Order By: Relevance
“…9 Its biological activity and interaction with polynucleotides have been recently reviewed. 10 Spectrophotometric measurements demonstrated that it forms dimers and multiple aggregates in water. The increase of the ionic strength or the presence of small amount of DNA was found to promote the association.…”
Section: Introductionmentioning
confidence: 99%
“…9 Its biological activity and interaction with polynucleotides have been recently reviewed. 10 Spectrophotometric measurements demonstrated that it forms dimers and multiple aggregates in water. The increase of the ionic strength or the presence of small amount of DNA was found to promote the association.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest that berberine may either directly bind duplex DNA by intercalation (27)(28)(29)(30) or inflict DNA damage indirectly by its interaction with topoisomerases I and II (28,(31)(32)(33). Other investigators also showed that berberine at 150 mg/ml was able to induce the rate of sister chromatid exchanges, which reflects homologous recombination repair, by several fold (34).…”
Section: Discussionmentioning
confidence: 99%
“…heterodimers among these proteins (29)(30)(31). The balance between the expression levels of the protein units (e.g.…”
Section: Discussionmentioning
confidence: 99%